A história da população de Luanda no período final do tráfico Atlântico de escravos, 1781-1844 - Curto, José C.; Gervais, Raymond R. (Africana Studia, 2020)
This article has two, inter-related objectives. First. by drawing upon a relatively large number of censuses relating to Luanda between 1781 and 1844. to show that it possible to reconstruct the pre-1900 population history of certain arcas of the African continent. Second. in the specific case of Luanda. the premier urban centre along the whole western coast of Africa for the export of slaves to the Americas, its population history can not be explained solely by factors such as high leveis of mortality resulting from drought and disease or slave ilight. Rather, during the period under consideration, the population history of this slaving port needs to be understood within lhe broader context of the South Atlantíc complex of which it was an integral part, especially the considerable weight of Luanda's major slave market on the opposite side of the ocean, Rio de Janeiro.